Hormone‐secreting adrenal tumours cause severe hypertension and high rates of poor pregnancy outcome; a UK Obstetric Surveillance System study with case control comparisons. (2nd November 2017) - Quartermaine, G; Lambert, K; Rees, K; Seed, PT; Dhanjal, MK; Knight, M; McCance, DR; Williamson, C
Abstract : Objective: To examine the management and outcomes of adrenal tumours in pregnancy. Design: A national observational, cohort study over 4 years using the UK Obstetric Surveillance System (UKOSS). Setting: Consultant‐led obstetric units. Patients: Women with phaeochromocytoma, primary aldosteronism or Cushing's syndrome diagnosed before or during pregnancy. Methods: Clinical features of UKOSS cases were compared with those of women with adrenal tumours reported from 1985–2015. Nested case‐control comparisons involving the UKOSS cases as well as those identified in the literature were performed for pregnancy outcome data using UKOSS controls with uncomplicated singleton ( n = 2250) pregnancy and data from the Office of National Statistics (ONS). Main outcome measures: Incidence, management and frequency of adverse maternal and offspring outcomes of adrenal tumours in pregnancy. Results: Fifteen pregnant women met the inclusion criteria: ten phaeochromocytoma, three primary aldosteronism and two Cushing's syndrome. All of the tumours had an incidence rate <2 per 100 000 pregnancies. Clinical symptoms were similar to those in non‐pregnant women due to the hormones released. All women had severe hypertension, and in those diagnosed in pregnancy prior to conception. There was a significantly increased risk of adverse pregnancy outcomes in affected women, with increased rates of stillbirth, preterm labour and operative delivery. Conclusions: Adrenal tumours are associated with increased risks for pregnant women and their babies. Data on these tumours to inform practice are limited and international collaborative efforts are likely to be needed. Tweetable abstract: Study of hormone‐secreting adrenal tumours in pregnancy linked with high BP and high rates of fetal morbidity. Abstract : Tweetable abstract Study of hormone‐secreting adrenal tumours in pregnancy linked with high BP and high rates of fetal morbidity.